Problem-Based Learning Model as an Effort to Improve Student Learning Outcomes in Islamic Education Learning at MAN 4 Pidie Jaya - Lafriah; Lailatul Mufarrokhah (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to enhance student achievement in the subject of Islamic Cultural History by implementing the Problem-Based Learning (PBL) model. The study follows a classroom action research design, consisting of four stages: planning, implementation, observation, and reflection. The participants were 32 students from MAN 4 Pidie Jaya. Data were collected through tests and observation. The tests assessed students’ academic performance, while observations were used to evaluate the learning activities of both teachers and students during lessons. The data were analyzed using both quantitative and qualitative descriptive methods. The findings reveal that the PBL model significantly improved student performance. This is reflected in the rise of average scores from 62.5 in the initial stage to 71.3 in the first cycle, and further to 78.6 in the second cycle. Additionally, the percentage of students meeting the Minimum Completion Criteria increased from 40% before the intervention to 65% in the first cycle and 85% in the second. Therefore, the PBL approach proves to be an effective alternative teaching strategy that not only boosts academic outcomes but also fosters greater student engagement in the learning process.